Effective Front-End Strategies to Reduce Waste on Construction Projects - Rundle, Peter G.; Bahadori, Alireza; Doust, Ken.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume outlines a progressively staged process focused on fostering a more effective, more efficient, and greener global construction industry. The research-based book commences with an evaluation of eight methodologies identified after a worldwide literature and compliance review. It is followed by a more detailed report on four of these options, with the ultimate objective of independent selection within the construction engineering community of a single most appropriate methodology as the approach for further, more-detailed investigation. The eight methodologies were selected against six key performance indicators developed as assessment criteria and include knowledge management, lean construction, construction contract procurement practices, optimal work duration on site, construction site waste, rationalization of construction safety regulations, sustainable construction labor force, and portfolio project development. A primary outcome of the selected methodology being a triple bottom-line benefit to key stakeholders, commercially and also to the ecology, along with the community at large. Front-end construction waste strategies to serve as best practices to minimize waste generated by construction projects was the methodology selected for detailed research. The text also covers the primary sources of construction waste. The book is ideal for civil and construction engineers as well as project developers; managers and public sector waste management specialists. Shines a light on the extremely important topic of the global construction's use raw materials and generation of waste; Fills a void the academic literature on the critical need to embrace front-end strategies to reduce waste on construction projects along with recovery, re-use, and recycling; Evaluates each of the solutions presented and their means of implementation; Encourages readership beyond the book's core audiences of engineers and site managers to government, environmental groups, and the larger community; Points to other areas of future practical research in construction waste management.
Introduction Description -- Long List of 8 Methodologies Description -- Short List of 4 Methodologies Description -- Authors Core Study Objectives Description -- Research Methods Description -- Results Description -- Findings Description -- Discussion -- Conclusion -- Recommendations -- Acknowledgements -- Conflicts of Interest -- Dedication.
Keywords: Construction industry -- Management; Pollution; Industrial Management; Building materials; Buildings -- Design and construction; Construction Management; Pollution; Industrial Management; Building Materials; Building Construction and Design